THE USE OF WORD WALL MEDIA IN TEACHING DESCRIPTIVE WRITING - Kurniasih, Winda; ., Regina; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research focuses on teaching writing descriptive text using Word wall as a teaching media. The aim of conducting this research is to investigate whether or not the use of word wall media is effective in writing descriptive text for the tenth grade students of SMA Koperasi Pontianak in the academic year 2014/2015. The researcher conducted a pre-experimental study with measurement as the technique of collecting data and written test as tool of collecting data. The sample of this study was 28 students. The research finding show that the mean score of pre-test is 49; which is categorized as â€œPoorâ€. Furthermore, the mean score of post-test was 72.14; which is categorized as â€œAverage to Goodâ€. Based on the data analysis, it was found that the effect size of this research is 2,38 it can be concluded that there is a significant effect in the use of word wall in teaching writing descriptive text in the Senior High School students. Â Key words: Word wall, descriptive text, pre-experimental Â Abstrak: Penelitian ini focus pada pengajaran menulis teks deskriptif yang menggunakan Word wall sebagai media pembelajaran. Tujuan melakukan penelitian ini adalah untuk mengetahui apakah word wall efektif atau tidak dalam pengajaran menulis teks deskriptif pada siswa kelas sepuluh SMA Koperasi Pontianak pada tahun ajaran 2014/2015. Penelitian dilakukan dalam bentuk penelitian pre-experimental menggunakan tehnik pengukuran sebagai tehnik pengolahan data serta tes menulis sebagai cara mengumpulkan data. Penelitian ini melibatkan sampel sebanyak 28 siswa. Hasil dari penelitian ini mendapatkan nilai rata rata pre-test nya adalah 49; termasuk kategori â€œrendahâ€. Kemudian, nilai rata-rata dari post-test adalah 72,14; termasuk kategori â€œrata-rata ke baikâ€. Berdasarkan analisis data, ditemukan bahwa ukuran efektifitas dari penelitian ini adalah 2,38 ini dapat disimpulkan bahwa ada efek yang yang signifikan dari penggunaan word wall dalam pengajaran menulis teks deskriptif pada siswa Sekolah Menengah Atas. Â Kata kunci: Word wall, teks deskriptif, pre-experimental